If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24a + -22 = -4 + 6a Reorder the terms: -22 + 24a = -4 + 6a Solving -22 + 24a = -4 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. -22 + 24a + -6a = -4 + 6a + -6a Combine like terms: 24a + -6a = 18a -22 + 18a = -4 + 6a + -6a Combine like terms: 6a + -6a = 0 -22 + 18a = -4 + 0 -22 + 18a = -4 Add '22' to each side of the equation. -22 + 22 + 18a = -4 + 22 Combine like terms: -22 + 22 = 0 0 + 18a = -4 + 22 18a = -4 + 22 Combine like terms: -4 + 22 = 18 18a = 18 Divide each side by '18'. a = 1 Simplifying a = 1
| 18r+5s-7t+19r+9s-4r= | | 6(-4-8x)-3x=-7(7x+6) | | 3/4x-5=1 | | 63x^3y^2=49x^2y | | 7=7-4n | | -3x-21=-6(1-2x) | | Xy=h | | 7=-3y-2 | | 2(5p+1)=-8(4p+6)-8p | | 3x+15=9x-21 | | 1.666+x=-20 | | y=9x+14y+6x+25 | | 22-r=74 | | y=9x+14andy+6x+25 | | z-5z=72-9-z | | rv3/s2 | | 33+1/3c=66 | | 2x^2+4x-49=0 | | -65(z-61)=z-61 | | 1.5x=.833+2 | | 77+75+76= | | 2x+4y-2y+x= | | (w+6)(w-2)= | | 2/9=x/36 | | 8-(x+3)=-2x+9 | | 0=-9k | | -x+32=54 | | 4/7=x/35 | | 4/7=?/35 | | 56=2(10+a) | | -5b-4b=1-5b | | ax-a^2-bx+b^2= |